Applying case reuse and Rule-Based Reasoning (RBR) in object-oriented application framework documentation: Analysis and design - Jani H.M.; Lee S.P. (2023)
The main objective of an object-oriented application framework is to promote the reuse of both design and code in the development of new applications. The use of a framework will significantly decrease the amount of time taken for developing new applications. However, new framework users find that the documentation provided along with a framework is usually not very effective for new users. So, in this paper, we decided to apply another form of reuse, which is information reuse, to framework documentation. In order to come up with new solutions to new problems posed by the framework users, our proposed documentation approach will reuse previously documented cases, which have solved similar framework usage problems in the past. This requires the documentation system to be capable of understanding and learning from past experiences. We believe that with the reuse of past cases for solving new problems, new framework users will be able to dramatically improve their software development performance. The use of rule-based reasoning and genetic algorithms will optimize the case search and case adaptation process. 2008 IEEE.